A Comprehensive Study of India’s Prison System: An In-Depth Analysis of Structural Development and Capacity Challenges - Ayisha Sidique, Kanchal Gupta (Journal of Informatics Education and Research, 2024)
The study of Prison System in India is a multifaceted narrative that reflects the Evolution of Societal Norms, Legal Frameworks, and Governmental Policies. This research provides a meticulous analysis of Prison System in India, spanning from Ancient times to the post-independence era. Tracing the roots of incarceration practices in Ancient India, the study explores the evolution of punitive measures and confinement methods. It studies the impact of British colonial rule on shaping the prison system, highlighting its initial alignment with imperial interests and subsequent attempts at reform during the Pre-Independence and Post-Independence. The consequences of overcrowding are scrutinized, encompassing living conditions, healthcare access, and rehabilitation efficacy. In evaluating recent policy initiatives and international benchmarks, the research identifies potential solutions within India’s Socio-Cultural context. By offering a comprehensive understanding of the historical trajectory and contemporary challenges, this study advocates for systemic reforms that prioritize human rights, fairness, and effective rehabilitation within the Indian criminal justice system. The paper endeavors to trace the historical trajectory of prisons in India, spanning from ancient practices to the present day, and subsequently, scrutinizes the challenges faced by the Indian prison system across its history. Exploring the evolution of prisons in India is of paramount importance. It allows us to unravel the roots of the contemporary prison system, shaped by a complex interplay of indigenous practices, colonial influences, and post-independence reforms. The findings contribute significantly to ongoing discussions on prison reform and underscore the urgency of addressing overcrowding for a more equitable and humane legal landscape.